The Effect Of Running Dictation To Improve Students’ Listening Skill At Eighth Grade Of MTS Al Jauhar - Khamimatu Zahro (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2025)
This research investigated the effect of using the running dictation technique on improving students’ listening skill at the eighth grade of MTS Al-Jauhar. The study employed a quasi-experimental design involving an experimental class (VIII E) taught using the running dictation technique and a control class (VIII B) taught using conventional methods. A total of 54 students participated in the research. The study utilized quantitative methods and data were collected through pre-tests and post-tests to evaluate students’ listening skills. Statistical analyses, including descriptive statistics, normality and homogeneity tests, and the Welch Two Sample t-test, were conducted using SPSS software. The findings revealed that the mean score of the experimental group significantly increased from 39.66 to 81.55, while the control group showed minimal improvement (40.00 to 40.24). The t-test result (t = -20.548, p < 0.05) confirmed a significant difference between the two groups, indicating that the running dictation technique effectively enhanced students’ listening abilities. It can be concluded that the running dictation technique is an effective, interactive, and engaging method to improve listening skills among junior high school students.